RISK FACTORS OF CHRONIC KIDNEY DISEASE - LODHI , MS; FAROOQ , B; QURESHI , ZH; MALIK , FA; KHAN , MJ (Biological and Clinical Sciences Research Journal, 2023)
The prospective study was conducted in Tertiary Care Hospitals from June 2022 to June 2023 to evaluate risk factors for CKD in the local population. Six hundred subjects were included in the study who were screened for the risk factors of chronic kidney disease. The participants were screened for CKD using a questionnaire. CKD-EPI equation was used for exploring disease burden. Results showed that CKD subjects were more likely male, older, urban residents, were obese or overweight, and had cardiovascular disease, hypertension, and diabetes compared to those without CKD. In subjects with CKD, the most common risk factors were diabetes(32%), hypertension (65%), and anemia (40%). Sensitivity analysis was done using CKD – EPI equation, and results were compared with the MDRD-3 equation. The prevalence of CKD, according to CKD-EPI, was 16%. Prevalence of CKD stages I, II, III, IV, and V was 9%, 4.5%,4.5%,1%, and 1%, respectively. People were not well aware of the status of their condition. Primary care centers should screen patients with diabetes and hypertension for kidney disease. Early detection can retard progression and improve outcomes.